2016
DOI: 10.1155/2016/8469428
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Algorithm and Fuzzy Logic Approach for Video Shot Boundary Detection

Abstract: This paper proposed a shot boundary detection approach using Genetic Algorithm and Fuzzy Logic. In this, the membership functions of the fuzzy system are calculated using Genetic Algorithm by taking preobserved actual values for shot boundaries. The classification of the types of shot transitions is done by the fuzzy system. Experimental results show that the accuracy of the shot boundary detection increases with the increase in iterations or generations of the GA optimization process. The proposed system is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Gradual sequences were obtained by computing the maximum and minimum difference sequences between the overall block and each block. These gradual sequences show more distinct parabolic shapes compared with variance sequence frames (Thounaojam et al, 2016).…”
Section: Finding the Minimum Distance Between Sequencesmentioning
confidence: 93%
See 1 more Smart Citation
“…Gradual sequences were obtained by computing the maximum and minimum difference sequences between the overall block and each block. These gradual sequences show more distinct parabolic shapes compared with variance sequence frames (Thounaojam et al, 2016).…”
Section: Finding the Minimum Distance Between Sequencesmentioning
confidence: 93%
“…In the perspective of visual aspect, video is a kind of three-dimensional signal in which two of them reveal the visual content in the horizontal and vertical frame direction, and the third one reveals the variations of the visual content over the time axis. SBD is mainly based on the representation of visual content, construction of continuity signal and classification of continuity values (Thounaojam et al, 2016;Tippaya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yoo et al [12] suggested the variance distribution of edge information as feature for gradual transition detection. By considering a block of frames, the edge strength is extracted using orthogonal vectors by [13]. This approach oversees the effects of fast motion and lighting in the video.…”
Section: Fig 1 General Structure Of a Videomentioning
confidence: 99%
“…They also considered compressed domain techniques like MPEG algorithms in their review, since the compressed domain has become ascendant in video analysis. The temporal video segmentation in compressed domain extracts the features from DCT coefficients and motion strength [21][22][23]. However, computational efficiency is high whereas, the histogram approaches are better in performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thounaojam et al [ 85 ] proposed a shot detection approach based on genetic algorithm (GA) and fuzzy logic. The membership functions of the fuzzy system were computed with the use of GA by considering pre-observed values for shot boundaries.…”
Section: Sbd Approachesmentioning
confidence: 99%